Hybrid Ideologies in Clinical Settings: Implications for Intervention of the Changing Landscape in Violent Extremism - Rousseau, Cécile (Perspectives on terrorism, 2024)
Practitioners are observing rapid transformations in the landscape of violent ideologies. To understand the role and importance of changing ideologies for preventive interventions, this article describes the prevalence of hybrid ideologies in a clinical sample of clients referred for attraction toward or involvement in violent extremism and documents clinicians’ perspectives. Results demonstrate that hybrid ideologies are common and suggest that both homogenisation and fragmentation processes associated with globalisation and digitalisation may explain the observed shift in ideological presentation. These changes may have significant implications for intervention and call for a redefinition of ideological categories and silo approaches in the field.